Surviving in a new host: Eight years of monitoring translocated aroids, bromeliads, and orchids in the Andean forests in Colombia - Benavides, Ana María; Calderón-Caro, Jennifer; Canal, Dubán (Frontiers in Forests and Global Change, 2023)
Vascular epiphytes are extraordinarily diverse in the tropical Andean region. Compared to trees and terrestrial herbs, epiphytes are more vulnerable to forest alteration due to their structural dependence on trees and environmental requirements. Based on experimental approaches for ecological purposes, monitoring air pollutants, and seeking propagation alternatives, the rescue and translocation of vascular epiphytes (mainly bromeliads and orchids) from a threatened forest to a safer forest has been recently conducted in Colombia. Preliminary assessments indicate that epiphytes benefit from such well-planned measures, and their mortality and survival might be associated with extrinsic and intrinsic factors, which remain to be understood. We evaluated the survival of 16 vascular epiphyte species after translocation into a secondary forest in Antioquia (Colombia) for 8 years. We assessed the role of intrinsic (foliar area, number of leaves, initial pseudobulbs, stems or rosettes, functional group, and epiphyte species) and extrinsic factors (host tree species, bark water-holding capacity, type of substrate, location on the host tree, nutrients, and hormone addition) and the effect of climatic variables on plant survival. The overall mortality rate in this study ranked 1–7% per year, and survival decreased annually, reaching 44% by the end of the 8th year. Host tree species and intrinsic factors such as the functional group and epiphyte species significantly affected the probability of survival. Bromeliads, in particular, exhibited high mortality, which their monocarpic growth form could explain. Another group of species showing high mortality were the miniature orchids, Masdevalia amanda and M. platyglossa, and are associated with short life cycles. Five host tree species appear to affect the survival of translocated epiphytes; however, the factors or characteristics involved remain unclear. A higher seasonality of precipitation was related to the percentage of overall mortality. This result indicates that extreme precipitation events or drought reduce epiphyte longevity. In conclusion, our study suggests that a wide range of epiphytes may be successfully translocated to secondary forests in the Colombian Andes and demonstrates that the effective introduction of epiphyte assemblages may be useful for ecological restoration efforts in Andean forests.